Timing in Speech : A Review of Literature - Savithri SR (Journal of All India Institute of Speech and Hearing, 1970)
The paper reviews the literature on durational models, role of duration in  speech perception and factors  affecting  the duration of speech sounds. In the course  of discussion, several areas warranting  further research have been identified. Further,  the paper  briefly  dwells  on  the  notions of ancient  Indian scholars  on durational models.